ROBUST MANGROVE CHANNEL ASSESSMENT FOR MANGROVE CHANNEL VULNERABILITY VALUATION: A CONCEPT - Khairul Naim Abd Aziz; Siti Syafiqah Hashim; Jamil Tajam; Fazly Amri Mohd; Muhammad Akmal Roslani; Sharir Aizat Kamaruddin; Zulkiflee Abd Latif; Khairul Nizam Abdul Maulud (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
Despite being a highly beneficial marine ecosystem that offers unique habitats and biodiversity opportunities, mangrove areas have significantly degraded in recent decades due to unsustainable use, particularly along creeks and channels. This degradation will eventually have an impact on the services provided by mangrove forests, with factors such as sea level rise and human activities being found to be contributing factors. Changes in channel morphology caused by these factors also lead to the loss of mangrove trees in bank areas. While such changes occur naturally over long periods, the increasing prevalence of ecotourism activities is accelerating their effects. Even though some valuations with complex assessment have been developed but, those complexity are not viable to be carried out easily by community and the assessment through the mangrove channel have not yet been well addressed. Thus, this paper proposed a feasible assessment focusing on mangrove channel that is robust and practical for implementation. The two main objectives of this study are to thoroughly investigate relevant parameters and to examine appropriately the parameters rank for mangrove channel vulnerability assessment. The proposed assessment should include six important parameters which signifies their importance to the mangrove channel environment. All parameters studied will be rank from one to five (lowest to highest) to indicates their contribution to the mangrove channel vulnerability. The total average scores of the parameters will determine the vulnerability status of a particular mangrove channel. Keeping track of the state of mangrove channels is crucial for achieving sustainable development, even in situations where climate factors are beyond our control. The proposed concept should be evaluated and perhaps it will be useful in the exploration of mangrove and brings mutual benefits between the community and the environment.